Experimental research of trit pseudorandom sequence generating method for cryptographic applications - Шелест, Михайло Євгенович; Гнатюк, Сергій Олександрович; Жмурко, Тетяна Олександрівна; Кінзерявий, Василь Миколайович; Юбузова, Халіча Ібрагімівна (Ukrainian Information Security Research Journal, 2017)
In the last few years, development of quantum cryptography has attracted the scientist’s attention. Researches passed from the theoretical level to introduction of ready commercial decisions. The main difference between the methods of quantum cryptography and traditional (symmetric and asymmetric) cryptography consists in use of absolutely different principles in the basis. The quantum cryptography does not depend on computing or other intruder opportunities, uses specific unique quantum particles properties and based on inviolability of quantum physics laws. Among the most developed technologies of quantum cryptography is worth noting quantum secure direct communication, which can transmit information by open channel without encryption - removing key distribution problem, but in these protocols each bit of information is confidential and intruder shouldn’t get it, that’s why requirements for protocols stability is much higher and require security amplification methods. Such method was previously developed by authors, but its implementation requires the use of reliable trit pseudorandom sequences. In this context, this study presents an experimental research of trit pseudorandom sequence generating method for cryptographic applications. For evaluating the effectiveness of this method was developed experimental methodology, which confirms the possibility of using trit sequences generated by the method for ensuring the stability of quantum cryptography qutrit protocols to non-coherent attacks and for other crypto-graphic applications in modern information and communication technologies.